The songs of realization (mgur ʼbum) of Śar-pa Rnal-ʼbyor and Gnas mchog ʼOl mo luṅ riṅ gi bkod pa ṅo mtshar rgya mtshoʼi gter (an account of the legendary land of Bon, ʼOl-mo Luṅ-riṅ, by Tshe-dbaṅ-tshul-khrims) and Bon saṅs rgyas dgoṅs ʼdus kyi rdzogs chen skor (a collection of Rdzogs-chen precepts of the Bonpo tradition revealed by Tshe-dbaṅ-rgyal-po) - Śar-pa Rnal-ʼbyor (Ngwang Sonam : distributor Tibetan Bonpo Monastic Centre, 1976)
Collection of texts of the Bonpo tradition.